2008
DOI: 10.1186/1475-2875-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving equity in malaria treatment: Relationship of socio-economic status with health seeking as well as with perceptions of ease of using the services of different providers for the treatment of malaria in Nigeria

Abstract: Background: Equitable improvement of treatment-seeking for malaria will depend partly on how different socio-economic groups perceive the ease of accessing and utilizing malaria treatment services from different healthcare providers. Hence, it was important to investigate the link between socioeconomic status (SES) with differences in perceptions of ease of accessing and receiving treatment as well as with actual health seeking for treatment of malaria from different providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 19 publications
4
45
0
Order By: Relevance
“…Onwujekwe et al, [30] 2008 Cost analysis Malaria tx For the Inyi, Udi, Oji and Nachi communities, there was a significant difference in tx costs across SES groups (most poor, average and least poor); mean total financial costs associated with malaria tx ranged from NGN196 (SD 334.5) to NGN935.3 (SD 3324.5)…”
Section: Extent and Trend Of Health Economic Studiesmentioning
confidence: 97%
“…Onwujekwe et al, [30] 2008 Cost analysis Malaria tx For the Inyi, Udi, Oji and Nachi communities, there was a significant difference in tx costs across SES groups (most poor, average and least poor); mean total financial costs associated with malaria tx ranged from NGN196 (SD 334.5) to NGN935.3 (SD 3324.5)…”
Section: Extent and Trend Of Health Economic Studiesmentioning
confidence: 97%
“…Nigeria like many other Sub-Saharan African countries is bedeviled with the problem of low level of access to proper treatment especially of common illness like malaria. (Onwujekwe, Uzochukwu, et al 2008). This is due mainly to the general poor state of the health system, high cost of health services, lopsided distribution of health facilities in favor of the urban areas and gross underfunding of the health sector resulting in lack of subsidies and exemptions to the poor.…”
Section: Malaria In Nigeriamentioning
confidence: 99%
“…In the Sub-Saharan Africa in general, a large proportion of the drugs consumed by the people are supplied by PMDs, . Other studies in Nigeria have shown that upon recognition of malaria symptoms, most people go to PMDs for treatment as they are the easily accessible, (Onwujekwe, et al, 2008, Oladepo, et al, 2008, and Khumbulani, et al, 2011.…”
Section: Most Preferred Alternatives Base On Utility Functionmentioning
confidence: 99%
See 2 more Smart Citations